INSULIN INJECTION TECHNIQUE: EVALUATING THE GAP BETWEEN GUIDELINE RECOMMENDATIONS AND CLINICAL PRACTICE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetes mellitus (DM) is a major chronic metabolic disorder with rapidly increasing global prevalence. In India, approximately 69.9 million individuals are living with diabetes, and nearly 3.2 million depend on insulin therapy. Improper insulin injection technique is a significant and modifiable contributor to poor glycemic control. Aim: To evaluate insulin injection practices among long-term insulin users and identify gaps between recommended guidelines and real-world clinical practices. Materials and Methods: This cross-sectional observational study was conducted in the Department of Endocrinology at a tertiary care center from January 2020 to December 2024. A total of 500 patients diagnosed with diabetes mellitus and receiving insulin therapy for a minimum duration of five years were enrolled during their first visit to our center. A FITTER-based structured questionnaire was used to assess knowledge and practices related to injection technique. Demographic data and HbA1c values were recorded. Multivariate logistic regression analysis was performed to identify predictors of poor glycemic control (HbA1c > 8%). Results: The mean age of participants was 58.4 years, and the mean HbA1c was 9.11%. Most participants had type 2 diabetes (81%). Nearly 47% were unaware of correct injection sites, and the thigh was the most commonly used site (61%), while only 17% used the abdomen. A majority were unaware of the correct injection angle (78%), needle length (71.6%), and insulin concentration differences (90.2%). Needle reuse was common, with an average reuse of three times. Only 18% waited 5–10 seconds before withdrawing the needle. Lipohypertrophy was observed in 12.6% of participants. Lack of structured training, needle reuse, improper site rotation, and lipohypertrophy were independently associated with poor glycemic control. Conclusion: There is a substantial gap between guideline-recommended insulin injection practices and actual patient behavior. Structured and repeated diabetes education programs are essential to improve glycemic outcomes and reduce injection-related complications.